Sensorless control of AC machines for low and zero speed operation without additional test signal injection - Raute, Reiko (2009)
This work considers the sensorless control of AC machines for the low and zero speed operation range. Two novel techniques have been developed that use the inherit nature of the inverter PWM to estimate the rotor position of the machine.